PENGUKURAN KEMISKINAN DENGAN PENDEKATAN WATER POVERTY INDEX: - Kristijanto, A. Ign.; Utami, Intiyas; Wahyono, Teguh; Jocom, Harry (KRITIS, 2016)
This article aims to measure poverty based on the perspective of water resource using the mix of qualitative and quantitative methods. The study was conducted in Salatiga which is rich of water resources potential. Although it has a highwater potential, distribution of raw water by the PDAM could only cover 40% households, while other households rely on springs in order to meet the needs of raw water. The water springs spreads in nearly 64 spots in Salatiga, however, they reduced to only 36 spots due to many factors. Some springs which contributes to large water flow are usually located in a settlement with limited access to good sanitation. Our study however, shows that the Water Poverty Index of Salatiga was 0.84 or 84% which indicates a good level of welfare and human resource quality of the people. This is also in alignment to the Human Development Index which was found to 77.13. Finally, the prosperity of the community and the human resource could be increased when the policy on water resource and environmental management is consistently implemented.